MORFOGENESIS EKSPLAN TUNAS EUCALYPTUS PELLITA F. MUELL SECARA IN VITRO PADA MEDIA MURASHIGE AND SKOOG DENGAN ZAT PENGATUR TUMBUH BENZIL AMINO PURIN - Ellok Dwi Sulichantini; Eliyani Eliyani; Alvera Prihatini Dewi Nazari (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
Eucalyptus pellita is fast growing species and have many advantages such as: pulp and paper industry raw material, building construction, charcoal, and medicine. The research was carried out to study plant morphogenesis from shoot explant of E. pellita F. Muell by in vitro technique. The experiment was conducted at Tissue Culture Laboratory, Agriculture Faculty of Mulawarman University from March until June, 2016.Single factor experiment was arranged in Completely Randomized Design with 10 replications. The factor was BAP concentrations (B) consisted of 1.00 mg BAP L-1 (b1); 2.00 mg BAP L-1 (b2); 3.00 mg BAP L-1 (b3); and 4,00 mg BAP L-1 (b4). The explants was innoculated on MS medium supplemented with BAP according to the treatments. Data analyzed by analysis of variance (anova) and continued by Least Significant Difference (LSD) test with level 5%. Results of the experiment showed that the BAP concentrations can promote shoot formation of E. pellita. Statistical analysis indicated that the effect of BAP concentrations significantly difference on number of shoots at 8 weeks after innoculation (WAI), shoot length, and number of leaves at 4; 6; and 8 WAI, however it’s no significantly difference on shoot formation time and number of shoots at 4 and 6 WAI. The highest number of shoots, shoot length, and number of leaves achieved by 4,00 mg BAP L-1.